Hetero-oligomer of dynamin-related proteins participates in the fission of highly divergent mitochondria from Entamoeba histolytica - Takashi Makiuchi (Nature Portfolio, 2017)
Abstract Entamoeba histolytica is an anaerobic parasitic protist and possesses mitosomes, one of the most highly divergent mitochondrion-related organelles (MROs). Although unique metabolism and protein/metabolite transport machinery have been demonstrated in Entamoeba mitosomes, the mechanism of mitosomal fusion and fission remains to be elucidated. In this study, we demonstrate that two dynamin-related proteins (DRPs) are cooperatively involved in the fission of Entamoeba mitosomes. Expression of a dominant negative form of EhDrpA and EhDrpB, and alternatively, repression of gene expression of EhDrpA and EhDrpB genes, caused elongation of mitosomes, reflecting inhibition of mitosomal fission. Moreover, EhDrpA and EhDrpB formed an unprecedented hetero-oligomeric complex with an approximate 1:2 to 1:3 ratio, suggesting that the observed elongation of mitosomes is likely caused by the disruption and instability of the complex caused by an imbalance in the two DRPs. Altogether, this is the first report of a hetero-oligomeric DRP complex which participates in the fission of mitochondria and MROs.